2015
DOI: 10.1371/journal.pgen.1004960
|View full text |Cite
|
Sign up to set email alerts
|

African Glucose-6-Phosphate Dehydrogenase Alleles Associated with Protection from Severe Malaria in Heterozygous Females in Tanzania

Abstract: X-linked Glucose-6-phosphate dehydrogenase (G6PD) A- deficiency is prevalent in sub-Saharan Africa populations, and has been associated with protection from severe malaria. Whether females and/or males are protected by G6PD deficiency is uncertain, due in part to G6PD and malaria phenotypic complexity and misclassification. Almost all large association studies have genotyped a limited number of G6PD SNPs (e.g. G6PD202 / G6PD376), and this approach has been too blunt to capture the complete epidemiological pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 36 publications
4
73
2
Order By: Relevance
“…We also examined the HbC variant, and the ABO, ATP2B4, and FREM3/GYPE loci, which have well-validated protective effects against severe malaria (Malaria Genomic Epidemiology Network, 2014, 2015) and found no evidence that they affected the association of G6PD variants with severe malaria (Figure 1—figure supplement 3). The available data did not allow us to analyse α thalassemia across all study sites, but recent analyses at individual study sites have shown no evidence of interaction between the malaria-protective effects of G6PD deficiency and α thalassemia (Manjurano et al, 2015; Uyoga et al, 2015).
10.7554/eLife.15085.005Figure 1.Summary of single SNP tests of association at all sites combined.( A ) Schematic of genes across the genotyped region plotted relative to evenly spaced positions of SNPs in (B).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the HbC variant, and the ABO, ATP2B4, and FREM3/GYPE loci, which have well-validated protective effects against severe malaria (Malaria Genomic Epidemiology Network, 2014, 2015) and found no evidence that they affected the association of G6PD variants with severe malaria (Figure 1—figure supplement 3). The available data did not allow us to analyse α thalassemia across all study sites, but recent analyses at individual study sites have shown no evidence of interaction between the malaria-protective effects of G6PD deficiency and α thalassemia (Manjurano et al, 2015; Uyoga et al, 2015).
10.7554/eLife.15085.005Figure 1.Summary of single SNP tests of association at all sites combined.( A ) Schematic of genes across the genotyped region plotted relative to evenly spaced positions of SNPs in (B).
…”
Section: Resultsmentioning
confidence: 99%
“…This is partly due to the genetic complexity of the locus, being X-linked with multiple deficiency alleles with the result that it has extensive allelic and phenotypic heterogeneity, and also to the fact that clinical and epidemiological studies have appeared to give conflicting results. An early study concluded that G6PD deficiency protects against P. falciparum malaria in heterozygous females (Bienzle et al, 1972) and this is supported by a number of more recent studies (Manjurano et al, 2012; Sirugo et al, 2014; Luzzatto, 2015; Manjurano et al, 2015; Uyoga et al, 2015). However other studies have indicated that the protective effect is present in both heterozygous females and hemizygous males (Ruwende et al, 1995; Clark et al, 2009; Shah et al, 2016) or that it is confined to hemizygous G6PD-deficient males (Guindo et al, 2007), or that there are no protective effects at all (Johnson et al, 2009; Toure et al, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…Three G6PD deficiency alleles are particularly common and relatively well studied: the A – allele found in much of sub-Saharan Africa; the Med allele found in the Mediterranean and Middle East; and the Mahidol allele found Myanmar and Thailand. The protective effects of these G6PD alleles are complicated, and are likely heterogeneous across study populations and the form of malaria considered (see Manjurano et al, 2015; Malaria Genomic Epidemiology Network, 2014, for recent discussion). The A – and Mahidol alleles are thought to offer some protective effects against Plasmodium falciparum and P. vivax in both heterozygote females and/or hemizygote males (Ruwende et al, 1995; Louicharoen et al, 2009; Manjurano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The protective effects of these G6PD alleles are complicated, and are likely heterogeneous across study populations and the form of malaria considered (see Manjurano et al, 2015; Malaria Genomic Epidemiology Network, 2014, for recent discussion). The A – and Mahidol alleles are thought to offer some protective effects against Plasmodium falciparum and P. vivax in both heterozygote females and/or hemizygote males (Ruwende et al, 1995; Louicharoen et al, 2009; Manjurano et al, 2015). Haplotype-based analysis of genetic diversity surrounding A –, Med, and Mahidol suggest that they have spread over the past few thousand years (Tishkoff et al, 2001; Slatkin, 2008; Saunders et al, 2005; Louicharoen et al, 2009), consistent with the age of other known malaria resistance alleles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation